MiR-22 contributes to the pathogenesis of patients with coronary artery disease by targeting MCP-1: An observational study. Issue 33 (August 2016) - Chen, Bairong; Luo, Liyun; Zhu, Weiping; Wei, Xiaoliang; Li, Songbiao; Huang, Yin; Liu, Mao; Lin, Xiufang
Abstract : Abstract: The aim of this study is to determine miR-22 expression levels in peripheral blood mononuclear cells (PBMCs) of patients with coronary artery disease (CAD) and to investigate whether MCP-1 expression is regulated by miR-22. miR-22 expression in PBMCs from 60 CAD patients including stable angina pectoris (SAP) (n = 29), unstable angina pectoris (UAP) or non-ST elevation myocardial infarction (NSTEMI) (n = 17), or ST-elevation MI (STEMI) (n = 14) and 20 non-CAD subjects by real-time polymerase chain reaction (qRT-PCR). The luciferase activity assays were employed to determine whether miR-22 binds to 3′UTR of MCP-1. miR-22 mimics and inhibitors were transfected into healthy PBMCs. MCP-1 mRNA and protein levels were determined by qRT-PCR and enzyme-linked immuno sorbent assay, respectively. The qRT-PCR results showed that miR-22 levels in PBMCs were decreased in CAD patients, and MCP-1 was augmented in CAD patients and was inversely correlated with miR-22 levels. The luciferase activity assays indicated that MCP-1 was a target of miR-22. Overexpression of miR-22 could significantly repress MCP-1 expression at both mRNA and protein levels in PBMCs, whereas inhibition of miR-22 showed the opposite effects. This study revealed that miR-22 is downregulated in PBMCs from patients with CAD and that miR-22 may participate in inflammatory response by targeting MCP-1, therefore contributing CAD.